Image_8.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Urmila, who works at the stall, thoroughly kneads the dough to ensure that the rice flour is evenly mixed with water. Kneading helps to develop the gluten in the rice flour, which gives the bhakri its texture and makes the dough supple and soft, which allows it to stretch.